Experimental and numerical simulation of paraffin-based ternary composite phase change material used in solar energy system. (September 2022) - Fang, Guihua; Sun, Pengbo; Zhao, Maosen; Zhang, Wentao
Highlights: Expanded graphite effectively improves the problem of nano-copper agglomeration. The thermal conductivity of the composite phase change material was increased by 9.5 times. The melting/solidification process of composite phase change materials were simulated. The heat storage and release efficiency were improved by adding expanded graphite and nano-copper. After 200 cycles, the composite phase change materials still have good properties. Abstract: A series of paraffin-based ternary composite phase-change materials (PCMs) were prepared by combining paraffin (PA) with expanded graphite (EG) and nano-copper (Cu) in a two-step method. The thermal properties of the composite PCMs were studied by establishing an experimental test system and a simulation model. The results showed that the network pore structure of EG restrained the agglomeration phenomenon of Cu and that the addition of Cu improved the thermal conductivity, heat storage and release rate of the PA/EG composite PCMs. When the PA and EG mass percentages were 93/7 and the mass fraction of Cu was 1.25%, the thermal conductivity and thermal diffusivity were 2.57 W/(m·K) and 1.72 mm 2 /s, respectively, which were 9.5 and 13.5 times higher than PA, and the latent thermal value reached the theoretical value. Cu significantly accelerated the phase-change process of the composite PCMs, and the storage and release heat-response rates increased by 152.17% and 100%, respectively. After 200 storage/release cycles, there was little additional effect on the phase-change temperature and heat storage capacity. Compared to pure PA, the performance of the composite PCMs improved significantly, indicating that these composite PCMs are suitable for passive solar heating.